Pathologic Response to Pretransplant Locoregional Therapy is Predictive of Patient Outcome After Liver Transplantation for Hepatocellular Carcinoma: Analysis From the US Multicenter HCC Transplant Consortium. Issue 4 (April 2020) - DiNorcia, Joseph; Florman, Sander S.; Haydel, Brandy; Tabrizian, Parissa; Ruiz, Richard M.; Klintmalm, Goran B.; Senguttuvan, Srinath; Lee, David D.; Taner, C. Burcin; Verna, Elizabeth C.; Halazun, Karim J.; Hoteit, Maarouf; et al.
Abstract : Objective: The aim of the study was to determine the rate, predictors, and impact of complete pathologic response (cPR) to pretransplant locoregional therapy (LRT) in a large, multicenter cohort of hepatocellular carcinoma (HCC) patients undergoing liver transplantation (LT). Background: LRT is used to mitigate waitlist dropout for patients with HCC awaiting LT. Degree of tumor necrosis found on explant has been associated with recurrence and overall survival, but has not been evaluated in a large, multicenter study. Methods: Comparisons were made among patients receiving pre-LT LRT with (n = 802) and without (n = 2637) cPR from the United States Multicenter HCC Transplant Consortium (UMHTC), and multivariable predictors of cPR were identified using logistic regression. Results: Of 3439 patients, 802 (23%) had cPR on explant. Compared with patients without cPR, cPR patients were younger; had lower Model for End-stage Liver Disease (MELD) scores, AFP levels, and neutrophil–lymphocyte ratios (NLR); were more likely to have tumors within Milan criteria and fewer LRT treatments; and had significantly lower 1-, 3-, and 5-year incidence of post-LT recurrence (1.3%, 3.5%, and 5.2% vs 6.2%, 13.5%, and 16.4%; P < 0.001) and superior overall survival (92%, 84%, and 75% vs 90%, 78%, and 68%; P < 0.001). Multivariable predictors of cPR included age, sex, liver disease diagnosis, MELD, AFP, NLR, radiographic Milan status, and number of LRT treatments (C-statistic 0.67). Conclusions: For LT recipients with HCC receiving pretransplant LRT, achieving cPR portends significantly lower posttransplant recurrence and superior survival. Factors predicting cPR are identified, which may help prioritize patients and guide LRT strategies to optimize posttransplant cancer outcomes. Abstract : Supplemental Digital Content is available in the text